Composite filler for shell damage repair and preparation method thereof
By using composite fillers, including specific proportions of resin, glycidyl ether, nanofiller and other components, the gravure and defect problems caused by bumps in the electronic product shell are solved, and the effective repair and aesthetic recovery of the shell is achieved.
Patent Information
- Application Number
- CN202510072774.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
AI Technical Summary
Gravure printing and defects caused by bumps in electronic product shells affect the aesthetics and service life, and the prior art is difficult to effectively repair.
A composite filler is prepared by a specific mixing and stirring process to form a filler that can effectively repair shell damage.
The filler can effectively smooth out the gravure and defects of the shell, restore the aesthetics and integrity of the shell, extend the service life of electronic products, and is suitable for a variety of substrates.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of repair fillers, and in particular to a composite filler for repairing shell damage and a preparation method thereof. Background Art
[0002] Laptops, tablets, LCD TVs and other electronic products are now indispensable tools in our daily life and work, which can bring great convenience to our life and work. Frequent use of electronic products will inevitably cause the surface of their shells to be worn or damaged. For example, in the use of a laptop, an inadvertent bump will cause dents, scratches or defects to its shell, especially the edge of the shell will produce concave marks when bumped. These concave marks or defects will affect the aesthetics of the shell, and long-term existence will also affect the service life of the shell, thereby affecting the overall electronic product. Therefore, there is an urgent need for a filler that can repair the damage to the shell, and the concave marks and defects caused by the bumps on the shell can be filled with fillers to restore the beauty of the shell while keeping the shell intact to avoid affecting the overall use of the electronic product. Summary of the invention
[0003] The purpose of the present invention is to provide a composite filler for shell damage repair and a preparation method thereof. The filler is used for filling and repairing damage to the shell of an electronic product. The filler can fill the concave marks and defects caused by bumps on the shell, thereby restoring the aesthetics of the shell while keeping the shell intact to avoid affecting the overall use of the electronic product.
[0004] To achieve the above-mentioned purpose, the present invention provides a composite filler for shell damage repair, comprising the following raw material components in parts by weight: 25-30 parts of matrix resin, 15-25 parts of octyl glycidyl ether, 10-18 parts of benzyl glycidyl ether, 32-40 parts of nano filler, 1-5 parts of aluminum hydroxide powder, 1-4 parts of silane coupling agent, 2-8 parts of polystyrene sulfonic acid powder, 0.1-0.6 parts of leveling agent, and 0.1-0.5 parts of defoaming agent.
[0005] Preferably, the raw material components include the following parts by mass: 27 parts of matrix resin, 17 parts of octyl glycidyl ether, 13 parts of benzyl glycidyl ether, 35 parts of nanofiller, 2 parts of aluminum hydroxide powder, 1 part of silane coupling agent, 4 parts of polystyrene sulfuric acid powder, 0.5 parts of leveling agent, and 0.5 parts of defoaming agent.
[0006] Preferably, the matrix resin is a water-based resin, and the water-based resin is one of an acrylic acid ester water-based resin, a polyurethane-acrylate copolymer, a fluorinated acrylic acid ester water-based resin, and an alkyd resin.
[0007] Preferably, the nanofiller is one of nano silicon flakes, nano alumina, and carbon nanotubes.
[0008] Preferably, the nano filler is nano alumina with a particle size of 10 nm.
[0009] Preferably, the silane coupling agent is one of γ-glycidyloxypropyltrimethoxysilane, mercaptopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
[0010] Preferably, the leveling agent is an organosilicon leveling agent, and the defoaming agent is a polyether defoaming agent.
[0011] A method for preparing a composite filler for shell damage repair comprises the following steps: S1, mixing the matrix resin, octyl glycidyl ether and benzyl glycidyl ether, and stirring them in a blender at 600 rpm for 10 minutes to obtain a standby material 1; S2, filtering the aluminum hydroxide powder in a slurry state, adding a silane coupling agent at 60° C. and stirring thoroughly to obtain a hydroxyl-modified aluminum hydroxide powder, which is the spare material 2; S3, after fully stirring the reserve material 1 and the reserve material 2, perform ultrasonic dispersion treatment to allow the reserve material 2 to fully dissolve into the reserve material 1, thereby obtaining the reserve material 3; S4, fully mixing the nano filler, polystyrene sulfuric acid powder and water to obtain a semi-solid nano aggregate material 4 having ion dispersion characteristics; S5. Mix the reserved materials 3 and 4, stir them uniformly at a constant temperature of 25° C. at a speed of 150 rpm for half an hour, seal the mixture and let it stand for 3 hours to obtain a filler.
[0012] The advantages and beneficial effects of the composite filler for shell damage repair and the preparation method thereof are as follows: 1. The present invention can fill the concave marks and defects caused by bumps on the shell by filling, thereby restoring the aesthetics of the shell and keeping the shell intact, avoiding affecting the overall use of the electronic product.
[0013] 2. The matrix resin of the present invention is a water-based resin, which has good adhesion to the substrate and can adapt to a variety of substrates to ensure long-term stability of the coating. The water-based resin dries quickly, shortens the drying waiting period of the filler, and is convenient to use.
[0014] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0015] The technical solution of the present invention is further illustrated by the following examples.
[0016] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0017] Unless otherwise defined, the equipment, materials, reagents and other substances used in the present invention can be obtained through commercial use.
[0018] Example 1 A composite filler for repairing shell damage comprises the following raw material components in parts by mass: 25 parts of matrix resin, 20 parts of octyl glycidyl ether, 16 parts of benzyl glycidyl ether, 32 parts of nano filler, 3 parts of aluminum hydroxide powder, 2 parts of silane coupling agent, 4 parts of polystyrene sulfuric acid powder, 0.2 parts of leveling agent and 0.3 parts of defoaming agent.
[0019] The matrix resin is a water-based resin, and its chemical formula is (C 11 H 12 O3)n, the water-based resin is an acrylic ester water-based resin.
[0020] The nanofiller is nano silicon flakes.
[0021] The chemical formula of silane coupling agent is X3Si (CH2) n Y, wherein X is a hydrolyzable group and Y is an organic functional group. The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0022] The leveling agent is an organic silicon leveling agent, and the defoaming agent is a polyether defoaming agent.
[0023] A method for preparing a composite filler for shell damage repair comprises the following steps: S1, mixing the matrix resin, octyl glycidyl ether and benzyl glycidyl ether, and stirring them in a blender at 600 rpm for 10 minutes to obtain a standby material 1; S2, filtering the aluminum hydroxide powder in a slurry state, adding a silane coupling agent at 60° C. and stirring thoroughly to obtain a hydroxyl-modified aluminum hydroxide powder, which is the spare material 2; S3, after fully stirring the reserve material 1 and the reserve material 2, perform ultrasonic dispersion treatment to allow the reserve material 2 to fully dissolve into the reserve material 1, thereby obtaining the reserve material 3; S4, fully mixing the nano filler, polystyrene sulfuric acid powder and water to obtain a semi-solid nano aggregate material 4 having ion dispersion characteristics; S5. Mix the reserved materials 3 and 4, stir them uniformly at a constant temperature of 25° C. at a speed of 150 rpm for half an hour, seal the mixture and let it stand for 3 hours to obtain a filler.
[0024] Example 2 A composite filler for repairing shell damage comprises the following raw material components in parts by mass: 30 parts of matrix resin, 18 parts of octyl glycidyl ether, 14 parts of benzyl glycidyl ether, 38 parts of nano filler, 5 parts of aluminum hydroxide powder, 3 parts of silane coupling agent, 5 parts of polystyrene sulfuric acid powder, 0.5 parts of leveling agent and 0.3 parts of defoaming agent.
[0025] The matrix resin is a water-based resin, and the water-based resin is a polyurethane-acrylate copolymer.
[0026] The nano filler is nano alumina with a particle size of 10 nm.
[0027] The silane coupling agent is mercaptopropyltrimethoxysilane.
[0028] A composite filler for repairing shell damage, wherein the leveling agent is an organic silicon leveling agent, and the defoaming agent is a polyether defoaming agent.
[0029] A method for preparing a composite filler for shell damage repair comprises the following steps: S1, mixing the matrix resin, octyl glycidyl ether and benzyl glycidyl ether, and stirring them in a blender at 600 rpm for 10 minutes to obtain a standby material 1; S2, filtering the aluminum hydroxide powder in a slurry state, adding a silane coupling agent at 60° C. and stirring thoroughly to obtain a hydroxyl-modified aluminum hydroxide powder, which is the spare material 2; S3, after fully stirring the reserve material 1 and the reserve material 2, perform ultrasonic dispersion treatment to allow the reserve material 2 to fully dissolve into the reserve material 1, thereby obtaining the reserve material 3; S4, fully mixing the nano filler, polystyrene sulfuric acid powder and water to obtain a semi-solid nano aggregate material 4 having ion dispersion characteristics; S5. Mix the reserved materials 3 and 4, stir them uniformly at a constant temperature of 25° C. at a speed of 150 rpm for half an hour, seal the mixture and let it stand for 3 hours to obtain a filler.
[0030] Example 3 A composite filler for repairing shell damage comprises the following raw material components in parts by mass: 28 parts of matrix resin, 20 parts of octyl glycidyl ether, 14 parts of benzyl glycidyl ether, 36 parts of nano filler, 4 parts of aluminum hydroxide powder, 1 part of silane coupling agent, 8 parts of polystyrene sulfuric acid powder, 0.6 parts of leveling agent and 0.4 parts of defoaming agent.
[0031] The matrix resin is a water-based resin, and the water-based resin is a fluorine-containing acrylic ester water-based resin.
[0032] The nanofiller is carbon nanotubes.
[0033] The silane coupling agent is N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
[0034] The leveling agent is an organic silicon leveling agent, and the defoaming agent is a polyether defoaming agent.
[0035] A method for preparing a composite filler for shell damage repair comprises the following steps: S1, mixing the matrix resin, octyl glycidyl ether and benzyl glycidyl ether, and stirring them in a blender at 600 rpm for 10 minutes to obtain a standby material 1; S2, filtering the aluminum hydroxide powder in a slurry state, adding a silane coupling agent at 60° C. and stirring thoroughly to obtain a hydroxyl-modified aluminum hydroxide powder, which is the spare material 2; S3, after fully stirring the reserve material 1 and the reserve material 2, perform ultrasonic dispersion treatment to allow the reserve material 2 to fully dissolve into the reserve material 1, thereby obtaining the reserve material 3; S4, fully mixing the nano filler, polystyrene sulfuric acid powder and water to obtain a semi-solid nano aggregate material 4 having ion dispersion characteristics; S5. Mix the reserved materials 3 and 4, stir them uniformly at a constant temperature of 25° C. at a speed of 150 rpm for half an hour, seal the mixture and let it stand for 3 hours to obtain a filler.
[0036] Example 4 A composite filler for repairing shell damage comprises the following raw material components in parts by mass: 27 parts of matrix resin, 17 parts of octyl glycidyl ether, 13 parts of benzyl glycidyl ether, 35 parts of nano filler, 2 parts of aluminum hydroxide powder, 1 part of silane coupling agent, 4 parts of polystyrene sulfuric acid powder, 0.5 parts of leveling agent, and 0.5 parts of defoaming agent.
[0037] The matrix resin is a water-based resin, and its chemical formula is (C 11 H 12 O3)n, the water-based resin is a fluorinated acrylic ester water-based resin.
[0038] The nano filler is nano alumina with a particle size of 10 nm.
[0039] The silane coupling agent is γ-aminopropyltriethoxysilane.
[0040] The leveling agent is an organic silicon leveling agent, and the defoaming agent is a polyether defoaming agent.
[0041] A method for preparing a composite filler for shell damage repair comprises the following steps: S1, mixing the matrix resin, octyl glycidyl ether and benzyl glycidyl ether, and stirring them in a blender at 600 rpm for 10 minutes to obtain a standby material 1; S2, filtering the aluminum hydroxide powder in a slurry state, adding a silane coupling agent at 60° C. and stirring thoroughly to obtain a hydroxyl-modified aluminum hydroxide powder, which is the spare material 2; S3, after fully stirring the reserve material 1 and the reserve material 2, perform ultrasonic dispersion treatment to allow the reserve material 2 to fully dissolve into the reserve material 1, thereby obtaining the reserve material 3; S4, fully mixing the nano filler, polystyrene sulfuric acid powder and water to obtain a semi-solid nano aggregate material 4 having ion dispersion characteristics; S5. Mix the reserved materials 3 and 4, stir them uniformly at a constant temperature of 25° C. at a speed of 150 rpm for half an hour, seal the mixture and let it stand for 3 hours to obtain a filler.
[0042] Water-based resin provides the main film-forming substance of the coating, giving the coating good adhesion, flexibility and weather resistance.
[0043] Octyl glycidyl ether acts as a diluent and crosslinker, reducing viscosity and improving coating flexibility and chemical resistance.
[0044] Benzyl glycidyl ether further enhances the hardness and gloss of the coating while improving adhesion and chemical resistance.
[0045] Nano-alumina particles as fillers significantly improve the hardness, wear resistance and heat resistance of the coating.
[0046] Aluminum hydroxide powder acts as a flame retardant to improve the fire resistance of the coating and also has a certain filling effect.
[0047] Silane coupling agents are used to enhance the bonding force between inorganic fillers and organic resins, improving the overall mechanical properties and durability of the coating.
[0048] Polystyrene sulfonic acid powder is used as a dispersant or thickener to help stabilize the distribution of nanoparticles in the system and give the coating certain conductivity or antistatic properties.
[0049] The fillers of Examples 1-4 were used to repair the housing of electronic products of the same material. Before repairing, a pigment consistent with the color of the housing was added to the fillers of Examples 1-4 and mixed evenly. After the repair was completed, the glossiness, adhesion, and yellowing resistance were tested and compared with the undamaged housing of the same material (comparative example). The test results are shown in Table 1.
[0050] Gloss test: The gloss data was obtained by testing at an angle of 60° using a micro gloss meter (BYK).
[0051] Adhesion test: Use 3M tape to stick on the surface of the filler after curing, pull it up at a 45° angle, and observe whether the filler is detached at the damaged edge: if the detachment is between 0 and 5%, it is 5B, and if it is between 5 and 20%, it is 0B.
[0052] Yellowing resistance test: Using UVA (340) lamp as the light source, the repaired test shell and the undamaged shell are placed in the test conditions to meet the temperature of (60±3)℃ and the irradiance of 0.68W / m 2 , dry (no condensation) fluorescent UV aging test box, and keep continuous light for 168 hours during the whole process. Take it out after the light exposure, compare it with the undamaged shell that has also been exposed to light, and measure the color change with a colorimeter. The color change value unit is △E*. The smaller the measured value, the better the yellowing resistance.
[0053] Table 1 Performance test results
[0054] The data in Table 1 show that the curing performance of the filler of the present invention can reach the performance of the shell material and can be used to repair the shell.
[0055] Therefore, the present invention adopts the above-mentioned composite filler for repairing shell damage and its preparation method, which can fill the concave marks and defects caused by bumps on the shell through the filler, restore the beauty of the shell, and keep the shell intact to avoid affecting the overall use of the electronic product.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A composite filler for shell damage repair, characterized in that: The invention comprises the following raw material components in parts by weight: 25-30 parts of matrix resin, 15-25 parts of octyl glycidyl ether, 10-18 parts of benzyl glycidyl ether, 32-40 parts of nano filler, 1-5 parts of aluminum hydroxide powder, 1-4 parts of silane coupling agent, 2-8 parts of polystyrene sulfonic acid powder, 0.1-0.6 parts of leveling agent and 0.1-0.5 parts of defoaming agent.
2. The composite filler for shell damage repair according to claim 1, characterized in that: The invention comprises the following raw material components in parts by weight: 27 parts of matrix resin, 17 parts of octyl glycidyl ether, 13 parts of benzyl glycidyl ether, 35 parts of nano filler, 2 parts of aluminum hydroxide powder, 1 part of silane coupling agent, 4 parts of polystyrene sulfuric acid powder, 0.5 parts of leveling agent and 0.5 parts of defoaming agent.
3. The composite filler for shell damage repair according to claim 1, characterized in that: The matrix resin is a water-based resin, and the water-based resin is one of acrylic acid ester water-based resin, polyurethane-acrylic acid resin copolymer, fluorine-containing acrylic acid ester water-based resin, and alkyd resin.
4. The composite filler for shell damage repair according to claim 1, characterized in that: The nano filler is one of nano silicon sheets, nano aluminum oxide and carbon nano tubes.
5. The composite filler for shell damage repair according to claim 4, characterized in that: The nano filler is nano alumina with a particle size of 10 nm.
6. The composite filler for shell damage repair according to claim 1, characterized in that: The silane coupling agent is one of γ-glycidyloxypropyltrimethoxysilane, mercaptopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
7. The composite filler for shell damage repair according to claim 1, characterized in that: The leveling agent is an organic silicon leveling agent, and the defoaming agent is a polyether defoaming agent.
8. A method for preparing a composite filler for shell damage repair according to any one of claims 1 to 7, characterized in that: The steps include: S1, mixing the matrix resin, octyl glycidyl ether and benzyl glycidyl ether, and stirring them in a blender at 600 rpm for 10 minutes to obtain a standby material 1; S2, filtering the aluminum hydroxide powder in a slurry state, adding a silane coupling agent at 60° C. and stirring thoroughly to obtain a hydroxyl-modified aluminum hydroxide powder, which is the spare material 2; S3, after fully stirring the reserve material 1 and the reserve material 2, perform ultrasonic dispersion treatment to allow the reserve material 2 to fully dissolve into the reserve material 1, thereby obtaining the reserve material 3; S4, fully mixing the nano filler, polystyrene sulfuric acid powder and water to obtain a semi-solid nano aggregate material 4 having ion dispersion characteristics; S5. Mix the reserved materials 3 and 4, stir them uniformly at a constant temperature of 25° C. at a speed of 150 rpm for half an hour, seal the mixture and let it stand for 3 hours to obtain a filler.